Age and parity with pre-cancer lesions in cervical cancer foundation of South Kalimantan Indonesia region 2016-2017 - Rizka Norazizah; Nidatul Khofiyah (Universitas 'Aisyiyah Yogyakarta, 2019)
Cervical cancer is a gynecologic cancer incidence and cause of death have the second highest in the world, estimated at 80% of cervical cancer cases occur in developing countries. Cervical cancer in its early stages rarely cause complaints and when women consult a medical 70% are at an advanced stage that it is difficult to cure. Cervical cancer is caused due to infection of human papillomavirus (HPV) and exacerbated by several risk factors including age and parity. The purpose of this study was to determine the relationship of age and parity with the incidence of pre-cancerous lesions of the cervix. This is a case- control study comparing cases and controls in each variable. The sample used in this study using a ratio of 1: 1 in 310 people in the control group and 310 as cases of people taken at random by means of the control group and the total sample in the case group. Data collection tools used books patient reports and statistical tests using Chi_Square. The results in this study found an increased risk for 2,049 times in women aged ≥ 35 years and 2,046 fold increased risk in women who have children ≥ 3 with the incidence of pre-cancerous lesions of the cervix. So there is a significant relationship between age and parity with the incidence of pre- cancerous lesions of the cervix. The results in this study found an increased risk for 2,049 times in women aged ≥ 35 years and 2,046 fold increased risk in women who have children ≥ 3 with the incidence of pre-cancerous lesions of the cervix. So there is a significant relationship between age and parity with the incidence of pre-cancerous lesions of the cervix. The results in this study found an increased risk for 2,049 times in women aged ≥ 35 years and 2,046 fold increased risk in women who have children ≥ 3 with the incidence of pre-cancerous lesions of the cervix. So there is a significant relationship between age and parity with the incidence of pre-cancerous lesions of the cervix..